2021
DOI: 10.3390/agronomy11061035
|View full text |Cite
|
Sign up to set email alerts
|

Application of Kaolin and Italian Natural Chabasite-Rich Zeolitite to Mitigate the Effect of Global Warming in Vitis vinifera L. cv. Sangiovese

Abstract: High temperatures and the anomalous distribution of rainfall during the growing season may have a negative impact on grapevine yield and berry composition. In recent years, many studies have focused on the application of agronomical techniques to reduce the negative impact of heat waves on secondary metabolites such as phenols. In particular, treatments with kaolin have shown positive effects on reducing canopy temperatures, enhancing the accumulation of anthocyanins. In regard to the above, three treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 61 publications
4
17
0
Order By: Relevance
“…Brillante et al [56] reported that pinolene treatment on grapes caused a decrease in sugar content and anthocyanin level compared to control. In addition, recent studies on Vitis Vinifera showed that treatments with kaolin have highlighted positive effects on reducing canopy temperatures, enhancing the accumulation of anthocyanins [57].…”
Section: Antioxidant Activity Of Polyphenolics Extractsmentioning
confidence: 99%
“…Brillante et al [56] reported that pinolene treatment on grapes caused a decrease in sugar content and anthocyanin level compared to control. In addition, recent studies on Vitis Vinifera showed that treatments with kaolin have highlighted positive effects on reducing canopy temperatures, enhancing the accumulation of anthocyanins [57].…”
Section: Antioxidant Activity Of Polyphenolics Extractsmentioning
confidence: 99%
“…Italian natural chabazite-rich zeolite was reported to have no influence on photosynthesis in treated leaves of olive [40] and grapevine [41]. After foliar application of Italian natural chabazite-rich zeolite, improved olive or raisin quality was reported for olive trees [40] and grapevine [41]. Therefore, the effects of foliar application of the selected SNNMs, natural zeolites and DE, on fruit tree leaves are still scarce and contradictory and need further investigation.…”
Section: Characterization Of the Used Siliceous Natural Nanomaterialsmentioning
confidence: 99%
“…Application of another siliceous nanomaterial, kaolin, as a reflective anti-transpirant [33] and a photosynthesis and gas-exchange promotor [34] enhances photosynthesis in sweet orange [35], red grapefruit [36], olive [34] and grape [37]. Photosynthesis inhibition was noted after kaolin dusting on tomatoes, apples [38], hazelnut and walnut [39], olives [40] and grapevine [41]. Italian natural chabazite-rich zeolite was reported to have no influence on photosynthesis in treated leaves of olive [40] and grapevine [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then again, elevated CO 2 (eCO 2 ), one driver of climate change, may change bunch architecture (i.e., longer bunches), which might affect sun exposure, and increase growth of secondary lateral shoots, but periods of high temperatures may weaken this effect (Wohlfahrt et al, 2018). Obviously, both statements neglect effects of adapted management practices (Stoll et al, 2010;Zheng et al, 2017;Gatti et al, 2018;Valentini et al, 2018Valentini et al, , 2021Bei et al, 2019;Lavado et al, 2019;Hunter et al, 2020;GutiĂ©rrez-Gamboa et al, 2021;Martinez De Toda, 2021;Naulleau et al, 2021;SchĂ€fer et al, 2021) and other limiting factors like reduced soil water availability (Lopes et al, 2018). Thus, eCO 2 might reduce sunburn risks in the later season because of shading berries by increased lateral leaf area, but high temperatures might attenuate the positive effect.…”
Section: Introductionmentioning
confidence: 99%